Variability of Anthoxanthum species in Poland in relation to geographical-historical and environmental conditions: isozyme variation - Drapikowska, Maria (Biodiversity: Research and Conservation, 2013)
Variation of 9 isozyme systems was studied in Polish populations of 3 species of the genus Anthoxanthum: the native A. odoratum s. str. L. and A. alpinum Á. Löve & D. Löve, as well as the alien A. aristatum Boiss. Results of this study show that A. odoratum is characterized by a high isozyme variability of lowland populations, weakly correlated with habitat type, and partial genetic distinctness of montane populations. Moreover, 5 isozyme markers have been identified (Pgi-2, Dia-2, Mdh, Idh, Pgm) for the allopolyploid A. odoratum. Populations of A. aristatum are highly polymorphic (P = 98%). The observed isozyme differentiation of its populations (FST = 0.087) is low and gene flow between them (Nm = 5.314) is high. The genetic variation reflects environmental variation only to a small extent and is not significantly related to the phase of chorological expansion of this species. Altitudinal vicariants, A. alpinum and A. odoratum, are characterized by morphological and isozymatic distinctness, indicating their reproductive isolation. In populations of A. alpinum, polymorphism is high (P = 76.92%), differentiation among populations is moderate (FST = 0.198), and gene flow between populations along the altitudinal transect (Nm = 1.709) is relatively low